Measurement of the Top Quark Pair Production Cross Section in Proton-Proton Collisions at root s=13 TeV - Khachatryan, V. (2016)
The top quark pair production cross section is measured for the first time in proton-proton collisions at root s = 13 TeV by the CMS experiment at the CERN LHC, using data corresponding to an integrated luminosity of 43 pb(-1). The measurement is performed by analyzing events with at least one electron and one muon of opposite charge, and at least two jets. The measured cross section is 746 +/- 58(stat) +/- 53(syst) +/- 36(lumi) pb, in agreement with the expectation from the standard model.